Therapeutic effect of Erythroxylum coca spp. ethanol extract in experimental iron-deficiency anemia in male Holtzman rats - Gonzales-Carazas, Evelyn F. (2013)
Coca leaf has been traditionally used for medical purposes and contains high iron levels. Objective: To determine the effect of Erythroxylum coca spp. ethanol extract in iron-deficiency anemia induced by iron-deficient diet in male Holtzman rats. Design: Experimental. Setting: Institute of Pathology Laboratory, Universidad Nacional Mayor de San Marcos. Biologic material: Eighteen weaned male Holtzman rats 16 days old. Interventions: Rats were allocated to three groups of six rats each: a) iron-sufficient group (IS) received 25 g/d of balanced diet for 7 weeks; b) iron-deficient group (ID) received 25 g/d of iron-deficient diet for 7 weeks; and, c) irondeficient/ E. coca extract group (ID-CE) received 25 g/d of iron-deficient diet for 7 weeks, and in the fifth week 18 g/d of E. coca extract were added. Main outcome measures: Serum hemoglobin level, weight and height. Results: At the end of the treatment, there was significant difference of hemoglobin in the ID-CE group (p=0.04). There was significant difference in serum hemoglobin levels between ID-CE and ID groups (p=0.0062). No significant difference was found in serum hemoglobin levels between ID-CE and IS groups (p=0.06). No significant difference was found in weight and height between ID and ID-CE groups (p=0.20 and p=0.23, respectively). Conclusions: E. coca had experimental antianemic effect supported by findings in the serum hemoglobin levels.